Prevalence and genotype distribution of hepatitis C virus in Mongolia: Systematic review and meta-analysis. (April 2021) - Chaabna, Karima; Dashzeveg, Delgermaa; Shagdarsuren, Tserendulam; Al-Rifai, Rami H.
Abstract: Objective: To characterize hepatitis C virus (HCV) infection epidemiology in Mongolia. Method: Publications on HCV antibody (Ab) and RNA prevalence, and/or genotypes/subtypes were systematically reviewed and reported following PRISMA guidelines. Random-effects meta-analyses and age adjustments were conducted to estimate the prevalence of Mongolians exposed to HCV (pooled HCV-Ab prevalence) by time period, sex, and at-risk populations; and to estimate the prevalence of chronically-infected HCV individuals. Results: The national pooled HCV-Ab prevalence was 12.3% in 2000–2009 and 11.2% in 2013. Sex-specific pooled prevalence appeared higher among females than males (14.0% versus 6.8%). Age-specific pooled prevalence significantly increased from 3.7% among children (aged 0–10 years) to 34.1% among people aged ≥50 years ( p < 0.001). Among the adult general population (low-risk population), the national age-adjusted prevalence was 8.1%. Age-adjusted chronic infection prevalence in adults was 6.0%. Among healthcare workers, pooled prevalence was 18.0%. Among patients with liver diseases, pooled prevalence was 53.7%. Among individuals engaging in risky sexual behaviors, pooled prevalence was 11.1%. The identified circulating genotypes/subtypes were 1b (58.0%), 2a (21.7%), and 1a (20.2%). Conclusion: The national HCV prevalence in Mongolia appeared to be among the highest worldwide. Higher prevalence in the clinical setting indicated potential ongoing HCV iatrogenic and occupational transmission. Additionally, HCV transmission in community settings should be investigated.